2016
DOI: 10.5658/wood.2016.44.6.890
|View full text |Cite
|
Sign up to set email alerts
|

Solid Bioenergy Properties of Paulownia tomentosa Grown in Korea

Abstract: Paulownia tomentosa is one of fast-growing wood species in Korea. In order to evaluate the solid bioenergy properties of Paulownia tree, this study examined the heating value, moisture content (MC), pH and proximate analysis of stem, branch, root, bark and leaf. The heating values of wood parts were slightly higher than those of bark and leaf, and that of branch was the highest among all the samples. The higher moisture content of bark and leaf referred to their lower heating value. Also, the pH of stem, branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Ethanol extractives accounted for 21%, whereas protein and ash represented a lower fraction. Qi et al [ 20 ] reported a similar ash content (2.8%) for Paulownia tomentosa bark, with 80% volatile matter content and 17% fixed carbon content.…”
Section: Resultsmentioning
confidence: 90%
“…Ethanol extractives accounted for 21%, whereas protein and ash represented a lower fraction. Qi et al [ 20 ] reported a similar ash content (2.8%) for Paulownia tomentosa bark, with 80% volatile matter content and 17% fixed carbon content.…”
Section: Resultsmentioning
confidence: 90%
“…According to Al-Sagheer et al ( 2019), paulownia leaf meal had 8.85% of ash which was close to our results related to f. PSA and f. PN. Qi et al (2016) determined ash content in leaves and barks of 6.0 and 2.89%, respectively. As reported Ganchev et al (2019), the ash content of the leaves of P. elongata was 14.94% which was higher than in the leaves of P. tomentosa in our study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the case of willow and poplar, ash accounts for 0.5–1.2% [37]. Previous research showed that Paulownia tomentosa has a 0.19–6% ash content depending on the plant part, with 6% in the leaves and 0.23% in the wood [38]. High ash content in the tested Oxytree material can be caused by a high leaf content of 66% compared to 34% being shoots.…”
Section: Discussionmentioning
confidence: 99%
“…The examined pruned biomass of Oxytree had about 4% more combustibles, compared to the Paulownia tomentosa wood from a research forest of Kangwon National University, Republic of Korea [38]. The mean HHV was 18,295 ± 31; slightly below values in the literature.…”
Section: Discussionmentioning
confidence: 99%